Financial Technology Literacy Impact on Gen-Z in Indonesia - Putra Utama, Doni; Dian Sumarna, Alfonsa (Dinasti Publisher, 2024)
The purpose of this study Financial Technology Literacy Impact on Gen-Z in Indonesia